2014
DOI: 10.1098/rspb.2013.2535
|View full text |Cite
|
Sign up to set email alerts
|

Social forces can impact the circadian clocks of cohabiting hamsters

Abstract: A number of field and laboratory studies have shown that the social environment influences daily rhythms in numerous species. However, underlying mechanisms, including the circadian system's role, are not known. Obstacles to this research have been the inability to track and objectively analyse rhythms of individual animals housed together. Here, we employed temperature dataloggers to track individual body temperature rhythms of pairs of cohabiting male Syrian hamsters (Mesocricetus auratus) in constant darkne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Thus effects of these nonphotic cues on rhythmicity in polar vertebrates are likely occurring through masking and/or the entrainment of peripheral circadian oscillators. Field and laboratory studies also indicate that the social environment can influence daily and circadian rhythms in numerous species (5,80,93), although the mechanisms that underlie social entrainment have yet to be identified.…”
Section: Nonphotic Entrainmentmentioning
confidence: 95%
“…Thus effects of these nonphotic cues on rhythmicity in polar vertebrates are likely occurring through masking and/or the entrainment of peripheral circadian oscillators. Field and laboratory studies also indicate that the social environment can influence daily and circadian rhythms in numerous species (5,80,93), although the mechanisms that underlie social entrainment have yet to be identified.…”
Section: Nonphotic Entrainmentmentioning
confidence: 95%
“…In hamsters, physiological and behavioural processes are influenced by both the circadian clock and social stimuli, although these influences act independently [15]. Strong evidence of social influence on the clock has been found in the gregarious Nile grass rat Arvicanthis niloticus [9], in hamsters [50] and in social insects [5]. For some species, social behaviour may have an important influence on the clock, whereas for other species, it does not [14].…”
Section: The Unexplained Variancementioning
confidence: 95%
“…We have previously reported that social influences on t likely depend on individuals being housed unrestrained in direct physical contact for a relatively long period of time [8]. A survey of the literature and the results from this experiment suggest that another crucial element is the number of individuals in the group-with 25 fish [3], 100 bees [5], 40 flies [6], many bats [4], and, in this experiment, five mice.…”
Section: Discussionmentioning
confidence: 83%
“…Notably, pair-housing naturally solitary male Syrian hamsters can alter the t's of the cohabitants but does not lead to significant synchronization [8]. The effects of housing hamsters in greater numbers, and whether the result would be temporal segregation [15] rather than synchronization, have yet to be tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation